2005
DOI: 10.1097/01.pec.0000159073.47691.38
|View full text |Cite
|
Sign up to set email alerts
|

Hyperpyrexia Among Infants Younger Than 3 Months

Abstract: Hyperpyrexia is rare among febrile infants younger than 3 months. One-third of infants with temperature > or =40.0 degrees C had SBI. Future management algorithms might include hyperpyrexia as a risk factor for serious infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 22 publications
0
8
0
1
Order By: Relevance
“…This is because in our study, children with temperature range of 39.5-40°C were much younger (70% < 24mths) while those with temperature >40°C were older (57% > 24mths), as shown in Table 1. Although hyperpyrexia has been documented to be associated with higher risk for sepsis, guidelines on management of febrile children recommends that, height of body temperature alone should not be used to identify children with high risk for bacterial infection but the age of the child should also be taken into account 6,7,16 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because in our study, children with temperature range of 39.5-40°C were much younger (70% < 24mths) while those with temperature >40°C were older (57% > 24mths), as shown in Table 1. Although hyperpyrexia has been documented to be associated with higher risk for sepsis, guidelines on management of febrile children recommends that, height of body temperature alone should not be used to identify children with high risk for bacterial infection but the age of the child should also be taken into account 6,7,16 .…”
Section: Resultsmentioning
confidence: 99%
“…The National institute for health and clinical excellence (NICE) guide lines for management of febrile children in the United Kingdom recommends empiric antibiotic be given to children with suspected serious bacterial infection. 6 Considering that the prevalence of bacterial infections among febrile children in ambulatory clinic setting is 1.1% in the United States of America, few febrile children would actually require empiric antibiotics prescription 7 .…”
Section: Introductionmentioning
confidence: 99%
“…The height of body temperature may have some diagnostic and prognostic implications. Some studies have attributed high grade fevers in infants to serious bacterial infections [33], although others have also shown that children with high fevers are at equally high risk for serious bacterial infections and for viral illness [34].…”
Section: Classification Types and Patterns Of Fevermentioning
confidence: 99%
“…However, they acknowledged that the predictive value of hyperpyrexia in identifying individual infants with serious bacterial infection is low. Stanley et al [19] also reported a high (38%) prevalence of bacterial infection among children with temperatures >40°C when compared with those with lower temperatures. Hyperpyrexia, especially in young infants, is known to be a risk factor for bacterial infection when assessing febrile children.…”
Section: Discussionmentioning
confidence: 95%